Spatial Spillovers in Metropolitan Areas: Evidence from Swiss Communes - Christoph A. Schaltegger; Simon Zemp (Center for Research in Economics, Management and the Arts (CREMA), 2003)
This paper investigates spatial spillovers in local spending decisions by using panel data of the Swiss communes in the canton of Lucerne during the 1990s. Due to the geographical fragmentation with a major central city and some 100 suburban communes within a distance from 4 to 55 kilometers to the center this area represents a particularly useful data base in order to test the relevance of spatial interactions in metropolitan areas. The empirical evidence confirms strategic interactions among suburban governments and the central city for public security spending. A 10% increase of the city's security spending leads to a 3% decrease in security spending of the suburban communes in the Lucerne area. For all other spending items, the empirical evidence suggests no quantitative and significant spatial spillover effects. The same applies for spatial spillovers in overall local spending between the Lucerne communes and the Lucerne central city.
Keywords: D72; H72; 330; spatial spillovers; strategic interaction; central city exploitation